Design and sense: implications of Damasio's neurological findings for design theory - Love, Terence (IADE, 2003)
The inclusion of human feelings and emotions presents a serious problem in the design research field. Traditional approaches, focusing on emotions, are problematic for design theory building and do not align with recent findings about human psycho-neuro-physiological functioning. This paper describes research aimed at improving the ways feelings and emotions are represented in theories about design cognition. The paper focuses on recent research findings of Antonio Damasio and colleagues and applies them to theory making about designing and the ways designed artefacts are perceived and used.